Sex chromosome degeneration, turnover, and sex-biased expression of sex-linked transcripts in African clawed frogs (Xenopus) - Song, Xue-Ying; Furman, Benjamin L S; Premachandra, Tharindu; Knytl, Martin; Cauret, Caroline M S; Wasonga, Domnick Victor; Measey, John; Dworkin, Ian; Evans, Ben J (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2021)
The tempo of sex chromosome evolution-how quickly, in what order, why and how their particular characteristics emerge during evolution-remains poorly understood. To understand this further, we studied three closely related species of African clawed frog (genus Xenopus), that each has independently evolved sex chromosomes. We identified population polymorphism in the extent of sex chromosome differentiation in wild-caught Xenopus borealis that corresponds to a large, previously identified region of recombination suppression. This large sex-linked region of X. borealis has an extreme concentration of genes that encode transcripts with sex-biased expression, and we recovered similar findings in the smaller sex-linked regions of Xenopus laevis and Xenopus tropicalis. In two of these species, strong skews in expression (mostly female-biased in X. borealis, mostly male-biased in X. tropicalis) are consistent with expectations associated with recombination suppression, and in X. borealis, we hypothesize that a degenerate ancestral Y-chromosome transitioned into its contemporary Z-chromosome. These findings indicate that Xenopus species are tolerant of differences between the sexes in dosage of the products of multiple genes, and offer insights into how evolutionary transformations of ancestral sex chromosomes carry forward to affect the function of new sex chromosomes. This article is part of the theme issue 'Challenging the paradigm in sex chromosome evolution: empirical and theoretical insights with a focus on vertebrates (Part I)'.
Keywords: Xenopus; Sex Chromosomes; recombination suppression; mužské pohlaví; pohlavní chromozomy; Sex Determination Processes; heterogamy; Transcription, Genetic; dosage tolerance; genetická transkripce; procesy určující pohlaví; ženské pohlaví; zvířata; Sex Characteristics; pohlavní dimorfismus; Female; comparative transcriptomics; Male; Animals